INFLUENCE OF COMPUTER ASSISTED INSTRUCTION ON PRIMARY EDUCATION IN NIGERIA - Amede Lucky (Indonesian Journal of Learning and Instruction)
This study examined the influence of Computer Assisted Instruction on Primary education in Nigeria. It was delimited to Apapa Local Government Area (LGA) of Lagos State. Three research questions guided the study. The descriptive survey design was utilized for the study. The population consisted of all Primary schools’ teachers in Apapa LGA of Lagos state. Simple random sampling technique was used to select ten Primary schools, while purposive sampling method was employed in choosing 15 Primary schools’ teachers in each of the sampled school in Apapa LGA of Lagos state. The instrument used to obtain information was the Questionnaire titled: Computer Assisted Instruction Inventory (CAII). The data collected were collated, coded and analyzed, using descriptive statistics and mean rating because of their appropriateness to the study. The investigation reveals that: The influence Computer Assisted Instruction on learning in Primary schools and the level of the awareness was indeed low. There were enormous challenges facing the utilization of Computer Assisted Instruction on learning in Primary schools in Apapa LGA of Lagos State. Base on the conclusion reached, the following recommendations were drawn: Governments and school authorities should make effort to provide Computer in schools and ensure of effective usage in teaching and learning. Teachers’ should be made to be aware of the importance of Computer Assisted Instruction on learning in Primary schools. Government should provide Computer Assisted Instruction services in Primary schools and that government should provide solutions to the challenges of Computer Assisted Instruction services in schools. Keywords: Computer Assisted Instruction; Primary education; Primary schools’ teachers.